Palliative radiotherapy combined with stent insertion to relieve dysphagia in advanced esophageal carcinoma patients: A systematic review and meta−analysis - Xu, Zhiyuan; Liu, Haonan; Li, Shengli; Han, Zhengxiang; Chen, Jingjing; Liu, Xiangting; Li, Qiang; Mu, Hong; Yuan, Jiaqi; Lu, Hailong; Jin, Peisheng; Yan, Xianliang (Frontiers in Oncology, 2022)
Introduction: Oesophageal cancer is one of the most aggressive malignancies with limited treatment options, thus resulting in a high morbidity and mortality. For patients with advanced oesophageal cancer, median survival is 3–6 months, with the majority requiring intervention for dysphagia. Objective: To compare the relief of dysphagia in patients with incurable esophageal cancer treated with stenting alone or a combination of stenting and palliative radiotherapy. Methods: The protocol of this study was pre-registered on PROSPERO (CRD42022337481). PubMed, Wan Fang, Cochrane Library, Embase, and Web of science databases were searched by us. The literature search, quality assessment and data extraction were conducted by 2 reviewers independently. The primary endpoints included median overall survival and dysphagia scores. Bleeding events, stent migration, and pain events were secondary outcomes. The meta-analysis results (the primary outcomes and secondary outcomes) were pooled by means of a random effect model or fixed effect model. Results: Nine studies with a total of 851 patients were included for this meta-analysis, including 412 patients in the stenting alone group and 439 patients in palliative radiotherapy after oesophageal cancer stenting group (ROCS group). ROCS group could significantly improve dysphagia scores (SMD: -0.77; 95%CI: -1.02- -0.51) and median overall survival (SMD: 1.70; 95%CI: 0.67-2.72). Besides, there were no significant differences between the two groups in bleeding events, pain events, and stent migration. Conclusion: Patients with dysphagia in advanced oesophageal cancer will benefit further from ROCS in median overall survival and dysphagia scores. However, there was no significant advantage in improving bleeding events, pain events, and stent migration. Therefore, it is urgent to find a better therapy to improve the adverse events in the future.